When Does World History Begin? (And Why Should We Care?) - Northrup, David (History compass, 2003)
Advances in evidence and understanding challenge the conventional view that history begins with written records. Nonliterate societies and unlettered social classes, not just the literate élite, are now standard subjects of historical inquiry. Moreover, advances in archaeology and other disciplines have made ‘prehistory’ knowable. Advocates of ‘Big History’ start history with the Big Bang, but a less radical beginning is the point at which humans first began to display modern esthetic and intellectual traits - a point that now seems to coincide with the evolution of biologically modern humans.